PsycEXTRA Dataset 1975
DOI: 10.1037/e535372008-001
|View full text |Cite
|
Sign up to set email alerts
|

Stress in air traffic controllers: Comparison of two air route traffic control centers on different shift rotation patterns

Abstract: Nonci This doouBinl it (IIMMIIJIHIXI nndn* UM «wniBwhip of th* DMUtaMBt of Tntnspoitetion iu the intentt of information owhtng^ Th» United no liability for its oontants or on thnoof. i" I Ttchnicol Report D«cum«ntotion Pogt I. ntpüti No. FAA-AM-75-7 2. Co¥*rnfn*nt Acctttien No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Validation of Findings From Houston. The next study was designed to replicate and clarify findings from the two studies comparing shift rotation schedules at the Houston tower (31). The earlier comparisons of the two schedules, the 5-day and 2-2-1, at the Houston facility had been hampered by a variety of problems, including the fact that no assessment of evening shifts was available for the 5-day schedule.…”
mentioning
confidence: 99%
“…Validation of Findings From Houston. The next study was designed to replicate and clarify findings from the two studies comparing shift rotation schedules at the Houston tower (31). The earlier comparisons of the two schedules, the 5-day and 2-2-1, at the Houston facility had been hampered by a variety of problems, including the fact that no assessment of evening shifts was available for the 5-day schedule.…”
mentioning
confidence: 99%
“…These studies compared stress levels, mood variations, subjective sleepiness, and the sleep logs of controllers on different shift rotation patterns to determine whether certain schedules caused problems for them. The results of these studies showed that, generally, there was no significant difference between the controllers' stress levels on different shifts, but night work caused highly rated subjective sleepiness and reduced hours of sleep during the work week (Melton, 1985;Melton et al, 1973;Melton et al, 1975;Saldivar, Hoffmann, & Melton, 1977;Smith, Melton, & McKenzie, 1971). demonstrated that shift workers never overcome the negative effects of shift work and that shift work insomnia is a persistent problem for those who are afflicted with it.…”
Section: Statement Of Problemmentioning
confidence: 98%
“…Controllers work a variety of shift work schedules, but some studies by the Civil Aeromedical Institute (CAMI) in the 1970s and 1980s indicated a controller preference for the type of rotation patterns that are now known to induce circadian dysrhythmia (Melton, 1985). These studies also indicated that controllers were actually experiencing some of the adverse effects characteristic of internal disassociation (Melton, 1985;Melton et al, 1973;Melton et al, 1975;Saldivar, Hoffman, & Melton, 1977).…”
Section: Statement Of Problemmentioning
confidence: 99%